Internet controlled robotic arm - Wan Kadir, Wan Muhamad Hanif; Samin, Reza Ezuan; Ibrahim, Babul Salam Kader (2012)
When we talk about robots, people tend to think that robots are only suitable to use in the industry or just for the scientist to test about new technologies. However, the main function of robots are to help humans in doing work either in the industries or just helping out doing normal household chores. To bridge the gap of the normal perception of “robots are for the industries only”, internet will be use. This paper presents the development of an internet controlled robotic arm. The movement of the robot arm can be controlled by a computer via the internet. This robot can be used to demonstrate that a robot can be used inside a home for daily human chores. The robot is controlled by Arduino Uno that interfaced with the internet using Arduino Ethernet Shield. Two type of analysis were done for this project that is servo motor analysis and accuracy test. The accuracy test shows that the results of the actual output of the servo motor as compared to the input send to Arduino Uno via internet is between 97% to 99%. This prototype of the robot showed that the operational was successful. This user friendly robot is expected to bridge the gap between robot and household chores.